Ibeji-Figur mit Umhang frontal fotografiert (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Africa; Art; Yoruba (African people); Wood-carving; Orisha religion; Yoruba (African people)--Religion; Sculpture; Photographs; Ibeji; Ibeji Figure; Orisha; Orisha Art; Yoruba Art; Wood Sculpture